Hempseed as a nutritious and healthy human food or animal feed source: a review. (27th August 2020) - Xu, Youjie; Li, Jun; Zhao, Jikai; Wang, Weiqun; Griffin, Jason; Li, Yonghui; Bean, Scott; Tilley, Mike; Wang, Donghai
Summary: Hempseed products are projected to receive great potentials due to the rapid growth in the US market. Industrial hemp has been an important crop for food, fibre and medicine applications. Hempseed products can be used as nutraceutical supplements and functional foods for human and can be applied for animal feed. This review provides a comprehensive summary of nutritional quality and health benefits of hempseed which is attributed to high levels of essential fatty acids and other PUFAs in the oil, with a rich source of essential amino acids in highly digestible protein. This review examines the impact of extraction methods on oil yield and bioactive compounds, nutrition value, and food application of hemp protein‐extracted products, including meal, protein isolate and protein concentrate. Recent research related to the understanding chemical composition, nutritional value, health benefits, processing impact, functional properties of hempseed products, and their application for food and feed is presented.